Огнеупорные хромсодержащие цементы на основе соединений щелочноземельных элементов - Корогодская, Алла Николаевна; Шабанова, Галина Николаевна (Національний технічний університет "Харківський політехнічний інститут", 2016)
Представлены результаты получения алюмохромитных цементов с повышенной прочностью и огнеупорностью. Установлено, что фазовый состав алюмохромитных клинкеров представлен алюминатами и хромитами щелочноземельного элемента. Разработанные алюмохромитные цементы в зависимости от фазового состава относятся к вяжущим материалам гидравлического (кальциевые), воздушного (бариевые) или воздушно-влажного (стронциевые) твердения, являются быстросхватывающимися, быстротвердеющими, высокопрочными материалами с высокой огнеупорностью. Сравнение эксплуатационных характеристик указывает на возможность замены традиционных высокоглиноземистых цементов на разработанные алюмохромитные в футеровках печей, а также при выполнении ремонтно-восстановительных работ методом торкретирования высокотемпературных агрегатов.

The results of alumochromite cements obtain with high strength and refractoriness are presented. It was found that the phase composition of alumochromite clinkers presented of alkali-earth aluminates and chromites. In the process of firing the starting raw material mixtures by solid phase reactions is the emergence of mixed crystals of alkali-earth aluminates and chromites, as well as the formation of limited solid solutions of substitution due to the structural similarity of the synthesized phases. This results in crystals with a chemical and structural defects d ue to the hydraulic system of which the activity is increased compared to the hydraulic activity of the aluminate phase. Designed alumochromite cements depending on the phase composition are hydraulic binder materials (calcium), air (barium) or moist air (strontium) hardening are fast setting, high-strength material with high refractoriness. Comparison of performance points to the possibility of replacing the traditional high-alumina cements developed alumochromite cements in furnace linings, as well as in carrying out repair works by shotcrete high-temperature units.

Представлені результати отримання алюмохромітних цементів з підвищеною міцністю і вогнетривкістю. Встановлено, що фазовий склад алюмохромітних клінкерів представлений алюмінатами та хромітами лужноземельного елемента. Розроблені алюмохромітні цементи у залежності від фазового складу відносяться до в‘яжучих матеріалів гідравлічного (кальцієві), повітряного (барієві) або повітряно-вологого (стронцієві) тверднення, є швидкотверднучими, швидкотужаючими, високоміцними матеріалами з високою вогнетривкістю. Порівняння експлуатаційних характеристик вказує на можливість заміни традиційних високоглиноземних цементів на розроблені алюмохромітні у футерівках печей, а також при виконанні ремонтно-відновлювальних робіт методом торкретування високотемпературних агрегатів.
Chromium-containing refractory cements based on alkaline earth elements compounds
Keywords: алюминаты; хромиты; цементы; сроки схватывания; прочность; огнеупорность; aluminates; chromites; cements; setting time; strength; refractoriness; алюмінати; хроміти; цементи; терміни тужавіння; міцність; вогнетривкість